Diversity of Echinoderms from Intertidal Zone in Mesra Beach, Gunungkidul, Special Region of Yogyakarta - Nithoghani Hafni, Zatun; Eprilurahman, Rury; Rachmanto, Darren Nicholas; Ayunda, Filda Mega; Zuhaida, Hasna; Ikhsan, Muhammad Nur; Ashari, Imelda Tri; Rahmanto, Darren Nicholas; Wibowo, Safira Pramesti (Berkala Ilmiah Biologi, 2025)
Indonesia is considered a country with significant marine biodiversity, which contains many fauna, including Echinoderms that inhabit both shallow and deep waters. The coast of Mesra Beach, Gunung Kidul, has a sandy and rocky terrain, which, in theory, will be a suitable habitat for benthic animals, including Echinoderms. Since Mesra Beach is a relatively new beach in Gunung Kidul, there needs to be more data available that contains information on the diversity of echinoderms living in its intertidal zone during the 2023 period. Therefore, the study is conducted to record the diversity of Echinoderms in the intertidal zone of Mesra Beach, Gunungkidul, Yogyakarta. Data was collected using systematic sampling with 16 1 x 1 plot distributed evenly in 4 transects. The presence of families Echinometridae (Echinometra mathaei, Heterocentrotus trigonarius), Ophiocimidae (Ophiocoma scolopendrina), and Stomopneustidae (Stomopneustes variolaris) are found during the research period.